Impact of Ocean Acidification on Ecosystem Functioning and Services in Habitat-Forming Species and Marine Ecosystems - Zunino, Serena; Libralato, Simone; Melaku Canu, Donata; Prato, Giulia; Solidoro, Cosimo (Ecosystems, 2021)
Abstract Ocean acidification (OA) is expected to impact habitat-forming species (HFS), with cascading effects on the whole marine ecosystem and related services that are seldom quantified. Here, the changes in HFSs biomass due to OA are modeled using a food web ecosystem model, and the trophic and non-trophic cascading effects on the marine community are investigated. The food web model represents a well-studied coastal marine protected area in the NW Mediterranean Sea where coralligenous reefs and Posidonia oceanica meadows constitute important HFS. The model is used to implement 5 scenarios of habitat degradation, that is, reduction of HFS biomass, induced by increasing OA and to quantify the potential changes in ecosystem properties and indicators of ecosystem services over the next 100 years. The changes in ecosystem indicators highlight a decrease in the size of the system and a reorganization of energy flows suggesting a high degree of ecosystem development. All the proxies for ecosystem services show significant decreases in their values. Although representing only a portion of the possible impacts of OA, the findings are consistent with the idea that ecological systems can react to OA effects to maintain the level of ecosystem development, but the new organization might not be optimal from an anthropocentric viewpoint.